Epigenetic Modulation by Lactylation in Sepsis: Linking Metabolism to Immune Dysfunction - Chen Y; Hu H; Wang C; Wu J; Zan J; Liu Y (Journal of Inflammation Research, 2025)
Yinghong Chen,1 Hanrong Hu,1 Congwei Wang,1 Junxuan Wu,1 Jie Zan,2 Yuntao Liu3 1Second Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2School of Biomedical and Pharmaceutical Sciences, Guangdong University of Technology, Guangzhou, People’s Republic of China; 3State Key Laboratory of Traditional Chinese Medicine Syndrome, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of ChinaCorrespondence: Yuntao Liu, Email iamliuyuntao@163.com Jie Zan, Email zanj@gdut.edu.cnAbstract: Lactate, traditionally viewed as a metabolic byproduct, is now recognized as a key regulator of immune and epigenetic processes in sepsis. A recently discovered post-translational modification, lactylation, utilizes lactate as a substrate and plays a crucial role in cellular regulation. Accumulating evidence suggests that elevated lactate levels contribute to immune dysfunction in sepsis by modulating the activity of various immune cells. This modification links metabolic changes to immune regulation, making it a crucial factor in sepsis progression. Understanding how lactylation is altered in sepsis unveils critical links between immunometabolism, epigenetic regulation, and disease pathophysiology. These insights also highlight the interplay between metabolic and epigenetic reprogramming during septic progression. As a result, lactylation has emerged as a promising biomarker and potential therapeutic target in sepsis. This review aims to summarize the latest findings on lactate metabolism, lactylation modifications, and their immunometabolic implications in sepsis.Keywords: sepsis, lactate, histone, lactylation